Answer:
no
Step-by-step explanation:
we have that
x + 3y = 6 -------> first equation
2x − y = 10
x + 3y = 6-----> substract x both sides
-x+x+3y=6-x
3y=6-x-----> divide by 3 both sides
y=(6-x) /3
y=2-(x/3)
y=-(x/3)+2
therefore
the answer is
negative one thirdx + 2
Answer:$50
Step-by-step explanation:
So we have the sweater that’s $30 with a sale of 60% of the original price.
That means $30=60% of the original
So
30=60%start with this
5=10% divide 6 by both sides to get 10%
50=100% times by 10 to get 100%, which is the original price.
So the original price of this sweater is $50
:D